Fine Mapping and Candidate Gene Identification for the CapUp Locus Controlling Fruit Orientation in Pepper (Capsicum spp.) - Solomon, Abate Mekonnen; Kim, Tae-Gun; Han, Koeun; Lee, Hea-Young; Patil, Abhinandan; Siddique, Muhammad Irfan; Ahn, Jeonghwan; Kang, Byoung-Cheorl (Frontiers in Plant Science, 2021)
The orientation of fruits is a distinguishing morphological feature of pepper (Capsicum spp.) varieties. The pendent (downward curved) growth of the fruit stalks, known as pedicels, is highly correlated with fruit weight and pedicel length. A previous genetic analysis revealed that the pendent fruit orientation is governed by a dominant gene, and incomplete inheritance is also observed in some Capsicum accessions. To identify and localize this gene, a single quantitative trait locus (QTL) analysis was performed on one F2 and two recombinant inbred line (RIL) populations, and a genome-wide association study (GWAS) was performed using a core collection. Common QTL regions associated with fruit orientation were detected on chromosome 12. A total of 187,966 SNPs were identified in a genotyping-by-sequencing (GBS) for GWAS analysis of 196 C. annuum, 25 C. baccatum, 21 C. chinense, and 14 C. frutescens accessions, representing the germplasm collection of Korea. The results of these analyses enabled us to narrow down the CapUp region of interest to 200–250 Mbp on chromosome 12. Seven candidate genes were found to be located between two markers that were completely cosegregated with the fruit orientation phenotype. The findings and markers developed in this study will be helpful for additional understanding of pepper fruit development and breeding for fruit orientation.